2011
DOI: 10.1002/app.34782
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy–nanocomposites with ceramic reinforcement for electrical insulation

Abstract: Ceramic nanoparticles, that is, SiO 2 , TiO 2 , and Al 2 O 3 nanoparticles, with increasingly high thermal conductivity (k), represent good candidates for improving the thermophysical properties of epoxy resins. In this study, the influence of filler addition on the thermal, mechanical, and dielectric properties were investigated by means of differential scanning calorimetry, dynamic mechanical analysis, and dielectric spectroscopy to measure k, storage and loss moduli, dielectric permittivity, and volume resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Yalan Wu 12 reported that the dielectric constant and dielectric loss values decreased with the increasing addition of NH 2 -POSS into original epoxy resin. Amendola, E 13 and S. S. Vaisakh 14 found the dielectric constant could be decreased with introduction of ceramic nano llers. Jiao, Jian 2 added novel organic-inorganic particles (denoted POSS-MPS) into the epoxy resin and the POSS-MPS/EP nanocomposites containing 5 wt% of POSS-MPS showed a lower dielectric constant (D k ¼ 3.66) and loss factor (D f ¼ 0.017) in comparison to pristine EP with the value of 4.03 and 0.031.…”
Section: Introductionmentioning
confidence: 99%
“…Yalan Wu 12 reported that the dielectric constant and dielectric loss values decreased with the increasing addition of NH 2 -POSS into original epoxy resin. Amendola, E 13 and S. S. Vaisakh 14 found the dielectric constant could be decreased with introduction of ceramic nano llers. Jiao, Jian 2 added novel organic-inorganic particles (denoted POSS-MPS) into the epoxy resin and the POSS-MPS/EP nanocomposites containing 5 wt% of POSS-MPS showed a lower dielectric constant (D k ¼ 3.66) and loss factor (D f ¼ 0.017) in comparison to pristine EP with the value of 4.03 and 0.031.…”
Section: Introductionmentioning
confidence: 99%
“…2) It is known that the thermal conductivity of resins can be enhanced by adding ceramic fillers, and many reports have been published with the aim of enhancing the thermal conductivity of resins by adding of alumina (Al 2 O 3 ), 3) carbon fibers, 4) nanotubes, 5) silicon carbide, 6) and nitride fillers.…”
Section: Introductionmentioning
confidence: 99%
“…It is also emerging as a dielectric material to substitute porcelain and glass insulators. 1,2 A major drawback of the epoxy polymer is its low thermal dissipation property due to poor thermal conductivity (l ¼ 0.2 W mK À1 ), high thermal expansion coefficient (a ¼ 66.5 mm m À1 C À1 ) together with weak thermal shock resistance and profusely poor crack propagation resistance that oen leads to catastrophic mechanical failures. These undesired thermo-mechanical properties ultimately restrict the use of this economically benign glassy polymer for engineering applications.…”
Section: Introductionmentioning
confidence: 99%